Optimasi microwave-assisted pretreatment dalam delignifikasi asam oksalat pada kulit kakao menggunakan response surface methodology (RSM) - Ahmad Fadhlul Kamal; Efri Mardawati; Eko Heri Purwanto; S. Rosalinda (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Cocoa (Theobroma cacao L.) pod husk is a solid waste originating from the cocoa beans processing industry in very abundant quantities. The components that make up the cocoa pod husk include cellulose, hemicellulose, and lignin. Cocoa pod husk has a large cellulose content, so it has the potential to be used as cellulose-based bioproducts such as bioethanol. This study aimed to determine the optimum power, irradiation time, and concentration of oxalic acid in the cocoa pod husk microwave-pre-treatment delignification process. The cacao pod husk used in this study is a forastero variety from Pakuwon, Sukabumi, West Java, Indonesia. Cocoa pod husk raw material contains lignin, cellulose, and hemicellulose, respectively 15.73%, 40.14%, and 19.33%. The optimal conditions obtained using the Response Surface Methodology (RSM) model with factors that affect the process are power, irradiation time, and concentration of oxalic acid with response levels of cellulose, hemicellulose, and lignin after microwave pre-treatment. The results of the optimum conditions of power, irradiation time, and concentration of oxalic acid in the microwave assisted-pre-treatment process were 450 Watt, 10 minutes, dan 1%, respectively. The optimum conditions in the delignification process resulted in the levels of lignin, cellulose, and hemicellulose, respectively, which were 8.10%, 39.37%, dan 21.40%. Based on the lignocellulosic test at optimum conditions, the lignin decreased by 48.506%, cellulose decreased by 1.918%, and hemicellulose content increased by 10.709%. The results indicated optimum conditions could be applied in bioethanol and xylitol production